2020
DOI: 10.1111/jfbc.13210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi‐frequency countercurrent ultrasound treatment on extraction optimization, functional and structural properties of protein isolates from Walnut (Juglans regiaL.) meal

Abstract: This study evaluated the effects of ultrasound treatment on walnut meal protein (WMP) extraction and techno‐functional properties. The Box‐Behnken Design (BBD) was adopted for the optimization of the traditional and ultrasound‐assisted extraction (UAE) processes. Standard protocols were used to assay the techno‐functional characteristics. The extraction models’ statistical results exhibited adequacy with the least desirability index of 95.8%. The UAE enhanced the WMP extraction yield, purity, and chemical scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Naa Yarley et al [25] also found that the polysaccharides yield from crude sorghum leaf with multi-frequency ultrasound increased by 26.69 %. Moreover, a large number of similar results have been reported under the use of multi-frequency ultrasound in recent years [26] , [27] , [28] , [29] , [30] , [31] . For the extraction of phenolic compounds from eggplant, although several studies have been performed by ultrasound [32] , [33] , [34] , [35] , there are very few works for describing the extraction process using multi-frequency ultrasound, as well as rarely exploring to optimize the extraction variables via uniform design approach.…”
Section: Introductionmentioning
confidence: 54%
“…Naa Yarley et al [25] also found that the polysaccharides yield from crude sorghum leaf with multi-frequency ultrasound increased by 26.69 %. Moreover, a large number of similar results have been reported under the use of multi-frequency ultrasound in recent years [26] , [27] , [28] , [29] , [30] , [31] . For the extraction of phenolic compounds from eggplant, although several studies have been performed by ultrasound [32] , [33] , [34] , [35] , there are very few works for describing the extraction process using multi-frequency ultrasound, as well as rarely exploring to optimize the extraction variables via uniform design approach.…”
Section: Introductionmentioning
confidence: 54%
“…Combining two or more frequencies in a single US system provides certain advantages due to the interaction between different US waves [59] as the combined influence of all the frequencies is higher than the effect of the sum of the individual frequencies [51] , resulting in a significant increase in cavitation yield [60] . Pre-treatments using dual frequency of 20/40 kHz in a combined working mode and pulse on and off-time of 5 and 2 s respectively, was carried out in a specially designed equipment comprising of controllers, two probes, a temperature regulating system, a reaction vessel, and a liquid circulating system ( Fig.…”
Section: Effects Of Uae Conditions When Applied To Alternative Protei...mentioning
confidence: 99%
“…Moreover, these treatments also achieved higher soluble protein contents compared to other treatments using the same frequency at other angles, with levels of 16.07 % higher soluble proteins compared to treatments at 40 + 20 kHz 0° and 19.02 % higher than those at 40 + 20 kHz 30° [44] . Multi frequency US models have also been effectively used for protein extraction from walnut meal [59] and the microalgae Chlorella pyrenoidosa [62] .
Fig.
…”
Section: Effects Of Uae Conditions When Applied To Alternative Protei...mentioning
confidence: 99%
See 1 more Smart Citation
“…Protein extraction is considered an effective method to improve the comprehensive utilization and economic value of walnut dregs. As a conventional method to extract proteins, alkali-soluble extraction has been extensively applied in protein extraction due to its advantages of operational simplicity and cost-effectiveness [7] . However, alkali-soluble extraction has some shortfalls, including large solvent consumption, low extraction efficiency, and high energy consumption [8] .…”
Section: Introductionmentioning
confidence: 99%